Rhodophana guandishanense (Entolomataceae, Agaricales), a new species from China - Yang, Cheng; Fan, Li (Phytotaxa, 2020)
Rhodophana guandishanense sp. nov. is described and illustrated, from North China. Morphologically, the new species is distinguished from other Rhodophana species by the combination of a glabrous orange pileus with a central depression, an absence of hymenial cystidia, and basidiospores ellipsoid to oblong, strongly undulate-pustulate, with 9–14 rounded angles or facets in polar view. Molecular phylogenetic analyses based on RPB2, ATP6 and TEF1 sequences are provided, which supports the position of the new species and its genus.